AUDIT QUALITY OF GOVERNMENT AUDITOR - Setiawaty, Agus (Jurnal Akuntansi Multiparadigma, 2013)
Abstract: Audit Quality of Government Auditor. This study explores the relationship between governmentâs auditorsâ personal characteristics and acceptance of dysfunctional behavior situational factors on governmentâs audit quality. Data collection was conducted by distributing questionnaires to 111 governmentâs auditors. The data was analyzed using PLS application. The results showed that governmentâs auditors who increasingly accept dysfunctional behavior tend to have characteristic of external locus of control and that governmentâs auditors with external locus of control tend to have low organizational commitment. Leadership style of the audit team leader during the audit process improved the governmentâs auditorsâ commitment to their organization which leads to high-quality audit.Abstrak: Kualitas Audit dari Auditor Pemerintah. Penelitian ini mengeksplorasi hubungan antara karakteristik personal dan faktor-faktor situasional penerimaan perilaku disfungsional auditor pemerintah pada kualitas audit pemerintah. Pengumpulan data dilakukan dengan mendistribusikan kuisioner pada 111 auditor pemerintah. Data dianalisa menggunakan aplikasi PLS. Hasil menunjukkan bahwa auditor pemerintah yang semakin menerima perilaku disfungsional cenderung memiliki karakteristik locus of control eksternal dan auditor pemerintah dengan locus of control eksternal cenderung memiliki komitmen organisasi yang rendah. Gaya kepemimpinan tim audit selama proses audit meningkatkan komitmen auditor pemerintah pada organisasi mereka yang mengarah pada kualitas audit yang tinggi.